Limited effects of increased CO2 and temperature on metal and radionuclide bioaccumulation in a sessile invertebrate, the oyster Crassostrea gigas. (19th December 2015) - Belivermiş, Murat; Warnau, Michel; Metian, Marc; Oberhänsli, François; Teyssié, Jean-Louis; Lacoue-Labarthe, Thomas
Abstract: This study investigated the combined effects of reduced pH and increased temperature on the capacities of the Pacific cupped oyster Crassostrea gigas to bioconcentrate radionuclide and metals . Oysters were exposed to dissolved radiotracers ( 110m Ag, 241 Am, 109 Cd, 57 Co, 54 Mn, and 65 Zn) at three pH (7.5, 7.8, 8.1) and two temperatures (21 and 24°C) under controlled laboratory conditions. Although calcifying organisms are recognized as particularly vulnerable to ocean acidification, the oyster did not accumulate differently the studied metals when exposed under the different pH conditions. However, temperature alone or in combination with pH somewhat altered the bioaccumulation of the studied elements. At pH 7.5, Cd was accumulated with an uptake rate constant twofold higher at 24°C than 21°C. Bioaccumulation of Mn was significantly affected by an interactive effect between seawater pH and temperature, with a decreased uptake rate at pH 7.5 when temperature increased (27 ± 1 vs. 17 ± 1 d −1 at 21 and 24°C, respectively). Retention of Co and Mn tended also to decrease at the same pH with decreasing temperature. Neither pH nor temperature affected strongly the elements distribution between shell and soft tissues. Significant effects of pH were found on the bioaccessibility of Mn, Zn, and 241 Am during experimental in vitro simulation of human digestion.